UMA TRAJETÓRIA DA PRODUÇÃO DISCURSIVA NO ESTATUTO DA ASMA: um acontecimento discursivo na constituição da entidade como lugar de resistência - SANTOS, Silvia Cleide Piquiá dos (2020)
This dissertation analyzes the speeches of the Statute of the Association of the Deaf of Maranhão (ASMA) from the assumptions of the French Discourse Analysis (AD) and the theoretical contributions of Michel Foucault. We intend to reflect on the events that go through the discourse and the constitution of ASMA, based on the materiality of statements in the three versions of the Statute (1980, 2000, 2012). In this perspective, the work aims to verify how the Association of the Deaf of Maranhão (ASMA) presents itself, discursively, as a place of resistance. Highlighting the main events (discursive and non-discursive practices) that engender, genealogically, the foundation of ASMA. As well as, the knowledge and powers that cross the institution's subjectivity and make it a place of resistance. In this sense, we will present the theoretical categories of AD: discourse, event, device, subjectivity practice. In this methodological path, we delimited the corpus in the Purposes of the three versions of the Statute that constitute the essence of the subjectivity of creation and performance of the association. We will reflect on the events surrounding the institution's discourse and the resonance of these effects. The first reflection starts from the discontinuity of the discourse of recognition of the Brazilian Sign Language (Libras), Law nº 10.436 / 2002 that covers the subjectivity of the subject and the deaf community, in the cultural perspective. This achievement reverberates effects of truths on the deaf subject that resulted in the production of political devices for linguistic inclusion such as the creation of the bilingual school. These events were motivated by the National Deaf Movement, organized by FENEIS, which reaches the association's discursive production and the knowledge-power network that permeates the Statute. We believe that the enunciative regularities associated with the events made it possible to elucidate the Statute's speeches and the emergencies that made ASMA a place of resistance for the deaf. These conditions are related to the mobilization of linguistic and cultural knowledge-powers that constitute the deaf subjectivity of the association, within a discursive order.